Nursing-based intervention to optimize the self-prescribed and the misuse of antibiotics among mothers of children less than 5 years - Sameer Hamdy Hafez; Sabry M. Tamam; Noha Ahmed Mohamed; Elwaleed Idris Sagiron; Yahya Hussein Ahmed Abdalla; Mohammed Ateeg Abdelrahman Ahmed; Sharfeldin Mohammed Shuib; Elsadig Eltaher Hamed; Mohamed Saied Harfoush; Mohammed Abdulrahman Alshahrani; Ahmad A. Alshehri; Ahmed Salah Ali; et al. (Elsevier, 2024)
Background: The fact that bacteria have no geographical boundaries has made bacterial resistance to antibiotics a worldwide issue that requires collaboration and unity to address. Aim: evaluate the effect of nursing-based intervention to optimize the self-prescribed and the misuse of antibiotics among mothers of children less than 5 years. Methods: A quasi-experimental design was used to conduct this study. The study was conducted in Maternal Child Health Centers in Mansoura City & Beni-Suef City, Egypt, 100 participants were included in the study. A structured interview questionnaire was used to collect the data, which consisted of five parts; socio-demographic data, knowledge questions about antibiotics and their resistance, attitude scale towards self-prescribed antibiotics, questionnaire on safe use of antibiotics, and patterns of self-prescribed antibiotic use. Results: 41 % of the study group used self-prescribed antibiotics more than 6 times in the previous 6 months and 100 % of them used them to treat fever and sore throat, followed by 76 % for vomiting and diarrhea. There were significant improvements in participants' knowledge, attitudes towards self-prescribed antibiotics, and safe use of antibiotics after implementing the nursing intervention. Conclusion: The nursing-based intervention was successful in attaining its objectives in improving the total knowledge, attitudes and practices of the studied group. Recommendation: Health education about appropriate antibiotic use should be approved as a part of the preventive services obtained for the mothers.